Choice of law for void contracts and their restitutionary aftermath: The putative governing law of the contract - CHONG, Adeline (Institutional Knowledge at Singapore Management University, 2007)
This chapter examines issues surrounding the concept of the putative governing law of the contract by studying its role in establishing a void contract and personal unjust enrichment claims arising in the aftermath of voidness. Questions arising from a contract, such as whether the parties have fulfilled their mutual obligations, or the interpretation of certain terms used in the contract, are referred to the governing law of the contract. It is clear that the putative governing law needs to be accorded some role in any solution which prizes pragmatism and certainty in determining voidness. The three possible laws are the objectively determined governing law of the contract, the lexlocus transactionis and the lex fori. The lex fori is the law that is best suited to play this neutral role: its role can be justified logically and jurisprudentially as well as for the reasons of justice between the parties and expediency. Void contracts are an oxymoron. They are ‘contracts’ which do not exist; in other words, ‘contracts’ which are, in fact, not contracts at all. Void contracts give rise to some of the most demanding issues of choice of law as they yield logically intractable problems which have to be resolved by reference to putative factors and concepts. There are two parts of the equation when looking at choice of law for void contracts : first, establishing voidness; and secondly, the aftermath of voidness. The first initial question of which law determines whether a contract is void is generally answered by the putative governing law of the contract. 1 Once a contract is adjudged void, a claim that may be pursued in its aftermath is a personal unjust enrichment claim. The general choice of law rule in this area is also the putative governing law of the contract. 2 Thus, the concept of the putative governing law of the contract plays a central role in both parts of the equation where void contracts are concerned.